2017
DOI: 10.3389/fmicb.2017.00850
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Fengycin-Type Antifungal Lipopeptides in Bacillus amyloliquefaciens in the Presence of the Maize Fungal Pathogen Rhizomucor variabilis

Abstract: Most isolates belonging to the Bacillus amyloliquefaciens subsp. plantarum clade retain the potential to produce a vast array of structurally diverse antimicrobial compounds that largely contribute to their efficacy as biocontrol agents against numerous plant fungal pathogens. In that context, the role of cyclic lipopeptides (CLPs) has been well-documented but still little is known about the impact of interactions with other soil-inhabiting microbes on the expression of these molecules. In this work, we wanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 54 publications
2
36
0
1
Order By: Relevance
“…Production of antimicrobials by rhizobacteria is one of the major mechanisms for its antagonistic activity against phytopathogens, and they have great application potential being used as biocontrol agents. It has been reported that lipopeptides are the main antifungal compounds produced by Bacillus during the interactions with fungi (Zihalirwa Kulimushi et al ., ). Antagonistic experiments showed that B. subtilis HS3 has significant antifungal activity against several phytopathogenic fungi (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…Production of antimicrobials by rhizobacteria is one of the major mechanisms for its antagonistic activity against phytopathogens, and they have great application potential being used as biocontrol agents. It has been reported that lipopeptides are the main antifungal compounds produced by Bacillus during the interactions with fungi (Zihalirwa Kulimushi et al ., ). Antagonistic experiments showed that B. subtilis HS3 has significant antifungal activity against several phytopathogenic fungi (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…In this sense, B. subtilis , secretes numerous secondary metabolites including the antibiotic compound subtilin, the bacteriocin subtilosin, lipopeptides as surfactins, plipastatins, and others, and the polyketide/nonribosomal peptide hybrid compound bacillaene (25). Many of these metabolites play dual roles as antimicrobial compounds and signaling molecules during interactions, participating in development modulation, biofilm formation and inhibition of virulence factors of competitor individuals (4, 26, 38). In a previous work, we isolated a strain of B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…One could think that the lack of surfactin is a mere consequence of the metabolic change that arise along with the phenotype variation experienced by BsA01 and that is not directly related to the antagonism per se . However, it has been suggested that surfactins could interfere with the activity of other lipopeptides with proven antifungal activity such as fengycins/plipastatins and iturins (38, 41). In a study, B. amyloliquefaciens FZB42 mutants selectively repressed in the synthesis of one or two types of lipopeptides revealed that the co-production of surfactin and fengycin lowered the global antifungal activity (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This family is mainly composed of fengycin A and B (Vanittanakom et al 1986) and plipastatin A and B (Umezawa et al 1986). Fengycin mostly displays antimicrobial activity against a range of yeasts and filamentous fungi (Zihalirwa et al 2017).…”
Section: Introductionmentioning
confidence: 99%